Identification of Antipsychotic Side Effects with Glassgow Antipsychotic Side-Effect Scale (GASS) - Dita Hasni; Vivinia Rahmi Andika Putri; Mutiara Anissa (Journal of Health Science and Prevention, 2020)
Schizophrenia is ranked 4th of the top 10 diseases that burden worldwide. If the population of Indonesia reaches 200 million, it estimates that around two million have Schizophrenia. Based on Data from the World Health Organization (WHO), it estimates that around 24 million people worldwide have schizophrenia.2 the American Psychiatric Association (APA) were reported the incidence of Schizophrenia in the United States is about 1% of the adult population with a total of more than 2 million people. Schizophrenic patients were treated by antipsychotic agents that act to inhibit dopamine receptors, especially D2, and also inhibit adrenergic acetylcholine receptors and serotonin 5-HT2A. It can manifest side effects like extrapyramidal syndrome, amenorrhea, drowsiness, and others. This research aims to the identification of antipsychotic side effects with Glasgow Antipsychotic Side-effect Scale (GASS). 100 schizophrenics in HB. Saanin Mental Hospital were participating in this descriptive study after fulfilling the criteria of inclusion and exclusion. This study used the GASS questionnaire to interview subjects who were signing informed consent and get an explanation about this study. In this study, 92% of subjects reported mild side effects. The frequent complaints were extrapyramidal effects, sedation and CNS effects, anticholinergic effects, and weight gain (93%,80%,70 0% and 70% respectively). We found women complained of the side effects more often (16.38 ± 5.275) than men (12.58 ± 5.484) significantly with the value P = 0.001. Gass instruments can use screening antipsychotic side effects. This study concludes the most side effects complaints being extrapyramidal and drowsiness, and women more commonly found side effects than men.